Effects of Climate Change on Women's Food Security in Mwea East Sub-County, Kirinyaga County, Kenya - Eva Mwai; Aloys Ojore; Nyumba Tobias (Eastern African Journal of Humanities and Social Sciences)
Climate change has had adverse impacts on people’s lives and the economies of nations across the globe. This research examined effects of climate change on food security of women in Mwea East sub County, Kirinyaga County. The study was conducted in Ngucwi sub Location, Murinduko Ward and explored how climate change events continue to threaten food security among women. The study used descriptive research design and integrated qualitative and quantitative approaches. The researcher used purposive sampling to select Mwea East sub County which has experienced frequency and severity of climate change events of drought. Cluster sampling was used to divide the sample among the different villages and systematic random sampling to select households in each village. Out of the population of 38,734 women of ages 18 years to 69 years; a sample size of 449 was calculated. A semi-structured questionnaire was used to collect data and key informant interviews and focus group discussions were used to gather qualitative information. Quantitative data from questionnaires was analysed using descriptive statistics and regression analysis while thematic and content analysis was used to analyse qualitative data. The Statistical Package for the Social Sciences (SPSS) Version 25 was also used as a tool for analysing data. The study found that climate change was negatively related to food security, a relationship which was statistically significant. The study findings may provide policy and decision-makers with useful information to guide the design of appropriate socio-economic programmes, plans and policies to protect women from the adverse effects of climate change.